2016
DOI: 10.1016/j.jpeds.2016.06.087
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation Profile Dynamics in Pediatric Patients with Cushing Syndrome: A Prospective, Observational Comparative Study

Abstract: Objective To evaluate the association between Cushing syndrome and hypercoagulability in children. Study design A prospective, observational study was performed of 54 patients with Cushing syndrome, 15.1 ± 3.9 years, treated at the National Institutes of Health Clinical Center. Coagulation profiles were taken before and 6-12 months after surgery and compared with 18 normocortisolemic children, 13.7 ± 3.6 years. Results At baseline, patients with Cushing syndrome had greater levels of the procoagulant facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
(25 reference statements)
0
6
0
Order By: Relevance
“…6,11,22 Several studies have identified peculiar alterations of coagulation and fibrinolysis in patients with endogenous hypercortisolism that may contribute to the development of thromboembolic events. 5,23 In particular, it has been hypothesized that a prothrombotic state may be fostered by increased levels of procoagulant factors such as factor (F) VIII 7,18,[24][25][26][27][28][29][30] and von Willebrand factor (VWF) 18,[25][26][27][31][32][33] levels, with a concomitant impaired fibrinolytic capacity, which mainly results from an elevation in plasminogen activator inhibitor 1 (PAI-1). 20,25,[27][28][29]31,34 Finally, Koutroumpi et al 35 confirmed the presence of a state of hypercoagulability in patients with Cushing's syndrome through an increase in thrombin generation, a global assay that measures the overall tendency of a plasma sample to form thrombin after initiation of coagulation.…”
Section: Effects Of Endogenous Hypercortisolism On Hemostasis: the Cushing's Syndrome Paradigmmentioning
confidence: 99%
“…6,11,22 Several studies have identified peculiar alterations of coagulation and fibrinolysis in patients with endogenous hypercortisolism that may contribute to the development of thromboembolic events. 5,23 In particular, it has been hypothesized that a prothrombotic state may be fostered by increased levels of procoagulant factors such as factor (F) VIII 7,18,[24][25][26][27][28][29][30] and von Willebrand factor (VWF) 18,[25][26][27][31][32][33] levels, with a concomitant impaired fibrinolytic capacity, which mainly results from an elevation in plasminogen activator inhibitor 1 (PAI-1). 20,25,[27][28][29]31,34 Finally, Koutroumpi et al 35 confirmed the presence of a state of hypercoagulability in patients with Cushing's syndrome through an increase in thrombin generation, a global assay that measures the overall tendency of a plasma sample to form thrombin after initiation of coagulation.…”
Section: Effects Of Endogenous Hypercortisolism On Hemostasis: the Cushing's Syndrome Paradigmmentioning
confidence: 99%
“…The physiological explanation to link hypercortisolism and hypercoagulability is not fully understood. In one study, level of factor VIII positively correlated with UFC levels (11, 58), (not observed in our meta-analysis). Obesity also confers a higher risk of VTE, but the risk in CS seems higher than in otherwise healthy obese patients who are at low risk (14).…”
Section: Discussionmentioning
confidence: 38%
“…After initial studies that suggested presence of a hypercoagulable state in patients with Cushing’s syndrome ( 39 ), spontaneous activation of the hemostatic system was consistently shown in patients with hypercortisolism. Increased circulating levels of fibrinogen ( 19 , 20 , 40 , 41 ), D-dimer ( 20 , 23 , 40 ), vWF ( 20 , 42 44 ), AT-III ( 19 21 , 44 , 45 ), protein C-protein S complex ( 21 , 22 , 41 , 45 ), and PAI-1 ( 19 , 20 , 41 ) were reported together with changes of additional coagulation factors and hemostatic tests ( 19 21 , 41 , 43 , 46 ) in several cross-sectional comparisons of patients with Cushing’s syndrome with healthy subjects. Some studies suggested that these changes could be more relevant in patients with ACTH-producing adenomas ( 44 ) and increased levels of procoagulants and antifibrinolytics were reported also in children with Cushing’s syndrome that resolved after surgical treatment ( 45 ).…”
Section: Discussionmentioning
confidence: 99%